An attitudinal study of academic staff in the humanities and social sciences - Curtis, Bruce (New Zealand Sociology, 2021)
This research note compares the attitudes of academic staff in the humanities and social sciences in New Zealand reported across two studies (2003 and 2019). Attitudes were evaluated through the ratings and rankings of 56 statements. It is argued that the changes in attitudes reported across the two surveys are a social reality, not just the product of the research instrument. In this article, I compare changes in the ratings and rankings of six statements relating to issues of professional control and being rated by non-academics, as well an enhanced commitment to Te Tiriti o Waitangi [Treaty of Waitangi] and greater diversity in hirings.